PENGARUH KEPERCAYAAN, KEPUASAN KONSUMEN, DAN NILAI YANG DIPERSEPSIKAN PADA LOYALITAS DAN KOMITMEN - Rintar Agus Simatupang (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
This research aims to analyze the influence of trust, consumer satisfaction, perceived value, and commitment in loyalty and to analyze the influence of trust, consumer satisfaction, and the perceived value toward commitment.There are 500 respondents used in this research. They were taken using convenience sampling. The confirmatory factor analysis is employed to find out the validity and reliability of the data. The multiple regression analysis is used to analyze the data.The result of this research shows that in the first analysis, the trust, the perceived value and the commitment positively influences the loyalty, whereas consumer satisfaction had no significancy influence on the loyalty; the second analysis shows that consumer satisfaction and the perceived value positively influence the commitment, whereas the trust had no significant positively influence on the commitment.